2021
DOI: 10.1016/j.transci.2021.103211
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about Coronavirus (COVID-19) and challenges for blood services among potential blood donors

Abstract: Background The Coronavirus- 19 disease pandemic had a significant impact on the blood supply around the world. Physical distancing measures and many other factors contribute to this impact. Misinformation about methods of disease transmission and lack of knowledge among potential blood donors may contribute to this. Aim To assess the knowledge and awareness of blood donors about COVID-19 as well as their reasons and fears that prevent them from donating blood during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…The majority of participants in this study were male, similar to gender distribution reported by the world health organization (WHO) and from other Asian countries [ 14 , 15 ]. The blood collection at blood centres reduced considerably worldwide due to the Covid-19 pandemic [ 2 , 3 , 7 ].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The majority of participants in this study were male, similar to gender distribution reported by the world health organization (WHO) and from other Asian countries [ 14 , 15 ]. The blood collection at blood centres reduced considerably worldwide due to the Covid-19 pandemic [ 2 , 3 , 7 ].…”
Section: Discussionsupporting
confidence: 82%
“…Around 65% believed that blood centre staff take these safety precautions. This is in concurrence with 70% satisfaction of participants with the measures initiated to reduce Covid-19 infection [ 15 ]. The staff adherence to the Covid related protocol during blood collection and post-donation care helped gain donors' confidence.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Due to the closure of schools, commercial and religious sites, the blood volume collect-ed at the New York Blood Center in the USA dropped by 75% from March 16 to March 22, 2020 [46]. A retrospective study in Saudi Arabia showed that the blood volume collected in the blood center decreased by 39.5% during the SARS-CoV-2 pandemic [45]. Since the outbreak of SARS-CoV-2, blood donation in Madrid has decreased by about 45% [47].…”
Section: Measures To Ensure Blood Supply During the Sars-cov-2 Pandemicmentioning
confidence: 99%